Acupuncture combined with moxibustion for insomnia after stroke: A protocol for systematic review and meta analysis. Issue 3 (22nd January 2021) - Sun, Junjun; Zuo, Zheng; Song, Ran; Bao, Xiongying; Zhu, Miansheng
Abstract: Background: Stroke is the main cause of death and disability in the world and insomnia is a common complication of stroke patients. Insomnia will not only seriously affect the prognosis and quality of life of patients with stroke, but even cause the recurrence of stroke. Many studies have proved that acupuncture and moxibustion can effectively improve insomnia symptoms. This study will systematically evaluate the effectiveness and safety of acupuncture combined with moxibustion in treating insomnia after stroke. Methods: The following 8 databases will be searched from the inception to October 31, 2020, including China National Knowledge Infrastructure Database (CNKI), Chinese Scientific Journal Database (VIP database), China Biomedical Literature Database (CBM), Wanfang Data Chinese Database, PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Allied and Alternative Medicine Database (AMED), Excerpt Medica Database (Embase). We will also search for ongoing trials from the World Health Organization International Clinical Trial Registration Platform search portal, Chinese Clinical Trial Register, Clinical trials.gov. In addition, the reference lists of studies meeting the inclusion criteria will also be searched for achieving the comprehensive retrieval to the maximum. All randomized controlled trials of acupuncture and moxibustion in treating insomnia after stroke will be included. Two reviewers will conduct literature screening, data extraction, and quality evaluation respectively. The main outcome is the Pittsburgh sleep quality index (PSQI), and the secondary outcomes include clinical efficacy, quality of life, and safety. RevMan V.5.4.1 will be used for meta-analysis. We will express the results as risk ratio (RR) with 95% confidence intervals (CIs) for dichotomous data and mean difference (MD) or standard mean difference (SMD) 95% CIs for continuous data. Results: This study will provide a comprehensive review of the available evidence of acupuncture combined with moxibustion in treating insomnia after stroke. Conclusion: The conclusion of our study will provide the updated evidence to judge the effectiveness and safety of acupuncture combined with moxibustion for the treatment of insomnia after stroke. Trial registration number: PROSPERO CRD42020216720.